Kecemasan Ibu Post Partum Penyintas Covid 19 - Ganda Agustina Hartati Simbolon; Tiur Romatua Sitohang (Malahayati Nursing Journal, 2022)
ABSTRACT The mother post pregnancy experienced anxiety during the covid-19 pandemic with symptoms such as anxiety, uncalmness, a bad feeling of covid-19 virus transmission and a fear of being unable to herself and her baby from the covid-19 virus transmission. Post mothers' concerns during the quarantine and procedures carried out during the covid-19 pandemic can affect thoughts and emotions and worsen the symptoms of depression. To understand the concerns of the mother post of the covid survivors 19. This type of research is a quantitative with a descriptive research design. The study population is the mother of the post survivors covid 19. The sampling technique is sampling samples. Anxiety counter measures using the questionnaire from the counter-anxiety scale.The vast majority of respondents are 20-35 years of age (63.3%), the majority of those with 73.3% high school education levels, most of whom are multipersonnel delivery types. Most of the post moms of covid 19 suffer from moderate anxiety (56.6%). The majority of the mothers post survivors covid 19 have concerns at 56.6%. Of respondents' concerns of covid -19 could be caused by the fact that the covid-19 is a new illness and has a global negative effect, resulting in confusion, anxiety and fear in society. The effects of covid 19 affect the concerns of the covid mother post of the covid survivors 19 and make the post mother of the covid survivors 19 feel the doubts, concerns, stress and frustration that are affecting the expenditure Keywords : Covid 19, Anxiety, Mother post variety, Covid survivors 19  ABSTRAK Ibu post partum mengalami kecemasan selama pandemi Covid 19 dengan gejala yang dialami seperti gelisah, tidak tenang, mempunyai firasat buruk terhadap penularan Virus Covid-19 dan memiliki ketakutan  tidak mampu dirinya dan bayinya dari penularan virus Covid-19. Kekhawatiran ibu post partum masa karantina dan prosedur-prosedur yang dilakukan selama pandemi COVID-19, dapat berpengaruh pada pemikiran dan emosi dan memperjelek gejala depresi. Mengetahui kecemasan ibu post partum penyintas Covid 19. Jenis penelitian kuantitatif desain deskriptif. Populasi adalah Ibu Post Partum penyintas Covid 19. Teknik pengambilan sampling adalah consecutive sample. Alat ukur kecemasan menggunakan kuesioner dari Depression Anxiety Stress Scale (DASS 21). Mayoritas responden berumur 20-35 tahun (63,3%), mayoritas tingkat Pendidikan SMA 73,3%, mayoritas jenis persalinan responden multipara.  Mayoritas Ibu post partum penyintas Covid 19 mengalami kecemasan sedang (56,6%). Mayoritas ibu post partum penyintas Covid 19 memiliki kecemasan sedang 56,6%. Kecemasan responden terhadap Covid -19 terjadi karena Covid-19 adalah penyakit baru yang berdampak negative pada masyarakat secara global, menimbulkan rasa bingung, cemas dan takut. Covid 19 berdampak terhadap Ibu post partum penyintas Covid 19 dan membuat Ibu post partum penyintas Covid 19 merasa ragu-ragu,  cemas,  stress serta  frustasi yang berdampak pada  pengeluaran ASI Kata Kunci: Covid 19, Kecemasan, Ibu post partum, Penyintas Covid 19